Bibliometric analysis of research on genus Etlingera: insights into its biomedical applications - Fazalda Annuar; Liza Noordin; Wan Amir Nizam Wan Ahmad; Ainul Bahiyah Abu Bakar; Anani Aila Mat Zin (Penerbit Universiti Kebangsaan Malaysia, 2025)
The genus Etlingera belongs to the family Zingiberaceae (Ginger family), comprising more than 100 species, which possess a substantial medicinal value. Their role in drug discovery is significant due to their bioactive compounds, including antioxidants, anti-inflammatory, antimicrobials, and anticancer. Research on this genus is primarily limited to in vitro and in vivo studies. Thus, there is a significant gap in the research in pharmacology and drug development. This analysis aimed to explore the trends of worldwide publications on the genus Etlingera until 2023. Data collection was performed by a literature search of the word ‘Etlingera’ based on title, abstract, and keywords. We retrieved 329 articles from the Scopus database, which were limited to research articles published in English. We used Harzing’s Publish and Perish software for citation metrics and analysis, and VOSviewer for data visualization. This data distribution in terms of the growth of publications, research areas, countries, organizations, top-cited articles, collaboration, and keywords were reported in this study. There was an increasing trend of publications on the genus Etlingera research after 2018, with Malaysia as the leading country. The top research area was ‘Agricultural and Biological Sciences’, and the most cited article was related to the methods of drying processes that best preserve or boost antioxidant levels. This bibliometric analysis highlights the pharmacological potential of the Etlingera plant, serving as a bridge between traditional and modern medicine. It also provides comprehensive data on the genus Etlingera research that may contribute valuable knowledge and suggest directions for future research.